2007
DOI: 10.1371/journal.pone.0001181
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Non-Stationary Diarrhea, Acute Respiratory Infection, and Malaria Time-Series in Niono, Mali

Abstract: BackgroundMuch of the developing world, particularly sub-Saharan Africa, exhibits high levels of morbidity and mortality associated with diarrhea, acute respiratory infection, and malaria. With the increasing awareness that the aforementioned infectious diseases impose an enormous burden on developing countries, public health programs therein could benefit from parsimonious general-purpose forecasting methods to enhance infectious disease intervention. Unfortunately, these disease time-series often i) suffer f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 44 publications
1
54
0
Order By: Relevance
“…3) shows a situation close to what the authors described in Mali with an initial increase in the number of ALRI cases during the hot and dry season and a second during the rainy season (Findley et al 2005;Medina et al 2007). A longitudinal study in a village in Burkina Faso showed that 44 % of fell ill during the 6 months of rainy season and 48 % during the 6 months of dry season.…”
Section: Impacts Of Desert Dust On Alri In Children Under 5 Years Oldsupporting
confidence: 68%
“…3) shows a situation close to what the authors described in Mali with an initial increase in the number of ALRI cases during the hot and dry season and a second during the rainy season (Findley et al 2005;Medina et al 2007). A longitudinal study in a village in Burkina Faso showed that 44 % of fell ill during the 6 months of rainy season and 48 % during the 6 months of dry season.…”
Section: Impacts Of Desert Dust On Alri In Children Under 5 Years Oldsupporting
confidence: 68%
“…Consequently, the proposed seasonal disease calendar ( Figure 3) and forecasts (Medina et al 2007) complement each other. [In fact, the seasonal factors described here have been employed to adjust forecasts in our previous study (Medina et al 2007). ] Forecast and calendar-based activities could be combined with the dual benefit of regular timing (seasonal disease calendars) and magnitude preparedness (forecasts).…”
Section: Discussionmentioning
confidence: 86%
“…Patient privacy was protected from inadvertent (or deliberate) violations because consultation records reflect aggregate data without personal identifiers (Medina et al 2007).…”
Section: Ethical Approvalmentioning
confidence: 99%
See 2 more Smart Citations